Increased Iron Overload and Glycated Hemoglobin in Diabetes Mellitus-П Patients in Sulaimani city - Mohammed, Sirwan Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2013)
The purpose of the current study was to assess the correlation between the iron overload and increased glycated hemoglobin (HbA1c) among some diabetic patients in Sulaimani outpatient clinics. The studied samples included 60 randomly selected patients diagnosed with diabetes mellitus-п, having mean age of 51 years. Oppositely, 20 nondiabetic persons (having normal blood glucose and HbA1c within the normal range (2- 6%) with mean age of (46) years; were enrolled as a control group. Serum ferritin (SF) was used for measuring iron storage status, correspondingly, blood glucose and mean values of glycemia, measured as glycated hemoglobin (HbA1c) are measured. The results of the current study revealed highly significant increasing of iron storage (P-value 0.001) and percentage of glycated hemoglobin (p 0.05) among the diabetic patients. Further studies with larger samples should be conducted to examine the possible role of iron overload in the emergence of diabetes.
Keywords: Iron overload glycated HemoglobinHbA1c Diabetes mellitusПReferences